Tyrosine kinase inhibitors in the treatment of metastatic renal cell cancer patients with early cytokine intolerance: TURCOS, a Turkish national, prospective observational study. (October 2021) - Benekli, Mustafa; Gumus, Mahmut; Ozkan, Metin; Dane, Faysal; Elkiran, Emin T.; Cicin, Irfan; Sevinc, Alper; Aliustaoglu, Mehmet; Isikdogan, Abdurrahman; Meydan, Nezih; Oksuzoglu, Berna; Ozyilkan, Ozgur; et al.
Objective: Cytokines have been the mainstay of treatment in metastatic renal cell cancer (mRCC) for decades before the introduction of tyrosine kinase inhibitors (TKIs), which dramatically changed the therapeutic landscape in these patients. This observational study was designed to evaluate use of TKIs in the treatment of cytokine-intolerant mRCC patients. Methods: A total of 151 cytokine-intolerant mRCC patients who were treated with TKIs (sunitinib, pazopanib and sorafenib) were enrolled in this prospective, non-interventional, multi-center observational study at 16 oncology centers across Turkey. Mean (SD) age was 61.3 (11.1) years and 74.8% were males. Data on duration of TKI treatment was the primary outcome measure. Additionally, overall response rate (ORR), progression free survival (PFS), overall survival (OS) and safety data were recorded. Results: Median duration of treatment was 8.2 months at a median follow up of 17.9 months. ORR and disease control rate were 12.5% and 70.8%, respectively. Median PFS and OS were 7.5 months (95%CI: 6.4–10.4) and 27.3 months (95%CI: 17.6–27.3) with no significant difference among three TKI agents in terms of treatment duration, ORR, PFS and OS. The most common adverse events excluding progression-which was the protocol requirement were diarrhea (13.6%), asthenia (13.6%) and hand-foot syndrome (12.6%). Dose modifications were required in 30.5% of the patients and 15% discontinued TKIs because of toxicity. Conclusions: Our findings confirm the efficacy and safety profile of TKIs in the first-line treatment of mRCC patients intolerant to cytokine treatment. There was no significant difference among three TKI agents in terms of treatment duration, ORR, PFS and OS. Trial registration: TURCOS ClinicalTrials.gov Identifier: NCT01585974. Registered April 25, 2012.